2011
DOI: 10.1126/science.1210718
|View full text |Cite
|
Sign up to set email alerts
|

Successful Transmission of a Retrovirus Depends on the Commensal Microbiota

Abstract: To establish chronic infections, viruses must develop strategies to evade the host’s immune responses. Many retroviruses, including mouse mammary tumor virus (MMTV), are transmitted most efficiently through mucosal surfaces rich in microbiota. We found that MMTV, when ingested by newborn mice, stimulates a state of unresponsiveness toward viral antigens. This process required the intestinal microbiota, as antibiotic-treated mice or germ-free mice did not transmit infectious virus to their offspring. MMTV-bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
344
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(367 citation statements)
references
References 48 publications
9
344
3
1
Order By: Relevance
“…Recent data have documented that mechanisms of cooperation between viruses and microbiota in the intestine exist. Indeed, it has been shown that immunity against mouse mammary tumor virus (56) and systemic pathogenesis caused by enteric viruses (57) are dependent on interactions between the viruses and the microbiota.…”
Section: Foxp3mentioning
confidence: 99%
“…Recent data have documented that mechanisms of cooperation between viruses and microbiota in the intestine exist. Indeed, it has been shown that immunity against mouse mammary tumor virus (56) and systemic pathogenesis caused by enteric viruses (57) are dependent on interactions between the viruses and the microbiota.…”
Section: Foxp3mentioning
confidence: 99%
“…Recent progress has been made to develop new culturing technologies so that we can grow previously ''unculturable'' organisms in the laboratory environment (Vartoukian et al 2010). We have expanded our view of the microbiome beyond bacteria and into the virome (viruses) (Minot et al 2011) and mycome (fungi) (Ghannoum et al 2010) and have begun to investigate the reciprocal interactions between these constituents (Kane et al 2011;Kuss et al 2011). The microbiome holds great potential for breakthroughs in translational medicine, including the promise of precision tools that will allow us to ''sculpt'' the microbiome with diet, prebiotics, probiotics, and targeted antibiotics to prevent and treat disease.…”
Section: Perspective and Future Directionsmentioning
confidence: 99%
“…For example, commensal microbiota provide immune inductive signals for antiviral immunity against mucosal influenza virus or systemic lymphocytic choriomeningitis virus (LCMV) infections, whereas commensal microbiota promote viral infection by murine leukemia virus or poliovirus (3,4,6,7). To determine the importance of commensal bacteria in defense against mucosal infection by HSV-2, we examined the outcome of intravaginal infection with 10 4 pfu of WT HSV-2 after administration of a combination of five oral antibiotics for 4 wk.…”
Section: Significancementioning
confidence: 99%